MENINGKATKAN HASIL BELAJAR PASSING BAWAH MELALUI PERMAINAN ‘BALI’ SISWA KELAS IV SD NEGERI NGEMPLIK WETAN 1 KECAMATAN KARANGANYAR KABUPATEN DEMAK (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2013)
This study uses classroom action research that consists of two cycles, and each cycle consistsof four stages: planning, action, observation and reflective. From the research conducted, showingthat the game is ’Bali’ to improve student learning outcomes. Average pretest score with49.67 percent students completeness 26.67%. In the first cycle, the average increased to 60.8and the percentage of completeness 40%, then the increase in cycle II with an average of71.87 and 76.67% completeness. In addition, the results also showed that through bali gamescan improve the skills of teachers. Average score of the original teacher skills in the first cyclewas 2.5 with sufficient criteria eventually increased to 3.2 with both criteria. This study aimsto improve learning outcomes passing under the Elementary School fourth grade studentsNgemplik Wetan I. The method used is a game of ’Bali’. From the research conducted, theaverage student pretest score 49.67 with 26.67% percent completeness. In the first cycle, theaverage increased to 60.8 and the percentage of completeness 40%, then the increase in cycleII with an average of 71.87 and 76.67% completeness. Conclusions This study shows that themethod of the game ’Bali’ to improve learning outcomes of students passing below the fourthgrade I Wetan Ngemplik State.